Evolution of ambiguity tolerance research a scientometric and bibliometric analysis - Rubiales-Núñez, José; Rubio, Andres; Araya-Castillo, Luis; Moraga-Flores, Hugo (Frontiers in Psychology, 2024)
The present study presents a retrospective bibliometric analysis, in which statistical methodology is applied to observe the quantifiable and qualitative evolution of the concept of tolerance to ambiguity (TA) over time. Additionally, a scientometric analysis is carried out using quantitative methods on scientific measurements and trends, aiming to establish the profile and identification of the concept, as well as its development in terms of research themes.The relevance of this study lies in the growing interest and development of research on tolerance to ambiguity. There has been a significant increase in studies across various fields, such as entrepreneurship, where psychological factors are relevant. It is important to identify how research on this concept has evolved in order to understand its impact on business and corporate domains.The research includes highly relevant literature such as Budner (1962), who specifies tolerance to ambiguity as a predisposition to perceive ambiguous situations as desirable, and Frenkel-Brunswick (1949), who explains it as a personality variable centered on the emotional and perceptual domain.The main focus of tolerance to ambiguity is the cognitive factor that directly influences the sensation of uncertainty and unease. This article obtained its data based on the eight indices comprising the main Web of Science collection. The research is limited from 1975 until December of the year 2022. A total of 378 articles were identified, reaching their peak scientific production during the year 2022 with 45 articles. Regarding citations, 7,773 were found, with the highest concentration in 2022, totaling 1,203 citations.This study highlights the growing exploration of the concept of tolerance to ambiguity (TA), emphasizing its importance across multiple disciplines in dealing with uncertainty. The research reveals that TA significantly influences decisionmaking and adaptability, underscoring its value in business and educational settings. By analyzing leading publications, authors, and research centers, the diversity of approaches to understanding TA is evident, indicating a promising direction for future research.